Simultaneous removal of fluoride and arsenic from water by hybrid Al-Fe electrocoagulation: process optimization through surface response method - Nyangi, Magori J.; Chebude, Yonas; Kilulya, Kessy F.; Andrew, Minu (Separation science and technology, 2021)
The electrocoagulation process using hybrid aluminum-iron electrode was used for the removal of arsenic and fluoride from water. The operation parameters; current density, initial pH, treatment time, initial concentration of arsenic and fluoride were optimized using the Box Behnken Design. The R 2 values for arsenic and fluoride removal were 0.83 and 0.96, respectively ensure a satisfactory of a developed quadratic model. At the optimized operation parameter of 9.90 mAcm −2 , pH 7.5; the Al-Fe EC reduced 16 mg/L and arsenic 200 µg/L to 1.12 mg/L and 9.60 µg/L, respectively in 50 minutes with an operating cost estimated to 0.99 $/m 3 .